Cholinergic Receptor Binding Profile of Hypericum perforatum L. and its Active Constituents - Hamurtekin, E.; Hamurtekin, Y.; Matucci, R.; Dei, S.; Baris, E.; Kazdagli, H. (Asian Network Scientific Information-Ansinet, 2022)
Background andObjective: Hypericum perforatum L (HP) is a popular herbal medicine with different pharmacological effects. This study investigated the possible cholinergic receptor affinities of HP extract and its three active constituents: hyperforin, hypericin and pseudohypericin. Materials and Methods: Radioactive compounds [3H]-N-methyl scopolamine used for muscarinic receptor binding studies in Chinese hamster ovary cells expressing human muscarinic receptor subtypes and [3H]-cytisine used for nicotinic receptor binding tests performed with mouse brains without a cerebellum. Muscarinic binding inhibition was observed with HP extract considerably for hM2 and hM5. Results: Hyperforin, hypericin and pseudohypericin showed a much lower affinity for muscarinic receptors at higher concentrations. The HP extract and its constituents did not produce any nicotinic receptor binding inhibition. Conclusion:These results suggested that post-junctional direct muscarinic receptor interaction may modulate some effects of HP extract and its constituents however different mechanisms apart from direct cholinergic receptor interaction might be considered for the pharmacological actions of hyperforin, hypericin and pseudohypericin.
Keywords: Hypericum perforatum L.; muscarinic receptors; nicotinic receptors; hyperforin; hypericin; pseudohypericin